Assessment of VANET multi-hop routing over an experimental platform. (25th September 2009) - Santa, Jose; Tsukada, Manabu; Ernst, Thierry; Mehani, Olivier, Antonio F. Gomez-Skarmeta
Experimental evaluation of Vehicular Ad-hoc Networks (VANETs) is still a remaining issue for most researchers. Some works carry out performance tests to evaluate the communication channel according to physical and MAC conditions. Only a few works deal with multi-hop experimentation, but practically none use routing protocols. In this paper an integral VANET testbed is evaluated, using 802.11b and a multi-hop network managed by the Optimised Link State Routing (OLSR) protocol. Up to four vehicles are used to study the VANET performance over different traffic environments and different metrics are considered to analyse the results, including a deeper analysis to track the routes followed by packets end to end. Results differ from traditional one-hop and static-route tests, presenting a more realistic study.